2010
DOI: 10.1111/j.1365-2559.2010.03577.x
|View full text |Cite
|
Sign up to set email alerts
|

Image analysis as an adjunct to manual HER‐2 immunohistochemical review: a diagnostic tool to standardize interpretation

Abstract: Dobson L, Conway C, Hanley A, Johnson A, Costello S, O’Grady A, Connolly Y, Magee H, O’Shea D, Jeffers M & Kay E (2010) Histopathology57, 27–38 Image analysis as an adjunct to manual HER-2 immunohistochemical review: a diagnostic tool to standardize interpretationAims:Accurate determination of HER-2 status is critical to identify patients for whom trastuzumab treatment will be of benefit. Although the recommended primary method of evaluation is immunohistochemistry, numerous reports of variability in interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 40 publications
7
57
0
Order By: Relevance
“…It has been mentioned that IHC 2+ result variability is principally caused by tissue quality, fixation time, type of antibody used and lack of standardization among users (3,12). In this sense, our experience indicates that IHC 2+ misevaluation depends on low Her-2 protein levels contained in samples analyzed, but principally on resolution capacity limitations of IHC methodology to quantify low target protein levels.…”
Section: Resultsmentioning
confidence: 84%
“…It has been mentioned that IHC 2+ result variability is principally caused by tissue quality, fixation time, type of antibody used and lack of standardization among users (3,12). In this sense, our experience indicates that IHC 2+ misevaluation depends on low Her-2 protein levels contained in samples analyzed, but principally on resolution capacity limitations of IHC methodology to quantify low target protein levels.…”
Section: Resultsmentioning
confidence: 84%
“…26 A recent large study 34 reported the rate of IHC 2þ at 24% by manual scoring and 14% were amplified by FISH, using the ratio of greater than 2.0. The rate of IHC 2þ by IA in one study 17 was 11.2% and FISH was positive in 26% of the cases. In our study, the FISHþ rate ranged from 1% to 14% (median, 5.3%), although a higher FISHþ rate was seen from 2008 onward; however, this was associated with higher numbers of IHC 2þ cases.…”
Section: Commentmentioning
confidence: 88%
“…9 One of the suggestions was that image analysis (IA) could be an effective tool for objective interpretation, and that validation and calibration of IA instrumentation is essential before implementation in the laboratory. Studies [10][11][12][13][14][15][16][17][18][19] have shown IA to be more objective and reproducible with higher correlation with the fluorescence in situ hybridization (FISH) assay. However, most of these studies included small series of cases and were not reflective of routine clinical practice.…”
mentioning
confidence: 99%
“…Hence, distinction between complete and incomplete membrane staining and cytoplasmic staining may be difficult. This may be one explanation for the high variation in concordance rates (75-91%) [16]. Recently, an IA system has been developed to assess the continuity of membrane immunoreactivity in addition to intensity, showing a concordance rate of 95% with FISH [16].…”
Section: Introductionmentioning
confidence: 99%